Обеспечение успешности обучения и воспитания с использованием педагогических инноваций - Байжанова, С.А. (My University, 2016)
Nowadays innovative processes involve all the areas of social entity. Basic principles of innovative educational institutions are humanization, democratization, individuation and differentiation. Progressive innovations appear on the scientific basis and help the practice on moving forward.
Keywords: innovation; pedagogic innovation; educational institution; ungraded school; innovative methods of education